Angle of Arrival Estimation in Smart Antenna for Wireless Communication - S. Jyothi Lakshmi, T.; Sandeep, S.; V. Rajya Lakshmi, Dr. (International Journal of Engineering and Technology, 2018)
Smart antenna technology has emerged as one of the most efficient techniques in supporting maximum communication link throughput. A smart antenna system with innovative signal processing can enhance the resolution of a signalâ€™s direction of arrival estimation. Successful design of Smart antenna is dependent on the efficient performance of DOA estimation algorithm as well as beamforming algorithm. This paper presents a comparative performance study between Classical Beam forming method, MUSIC (Multiple Signal Classification), MVDR (Minimum Variance Distortion less Response) which are different direction of arrival algorithms used in linear antenna array. The objective is to analyse and compare these algorithms and determine which provides maximum efficiency.Â Â